Development of a Behavioral Assessment of Emotional Perspective Taking Skills in Adults. - Garcia-Zambrano, Sebastian; Jacobs, Eric; Baires, Natalia; Garcia, Yors (Psychological Record, 2025)
Emotional perspective taking (EPT) is defined as the ability to recognize an emotion experienced by another person (Harwood & Farrar British Journal of Developmental Psychology, 24(2), 401–418, 2006), and to relate the emotion with the situation that evokes it (Cutting & Dunn Child Development, 70(4), 853–865, 1999). From a relational frame theory (RFT) perspective, the development of perspective taking skills is underpinned by the ability to respond to a combination of deictic contextual cues. Deictic framing refers to the process of responding to spatial, temporal, and interpersonal relations. The purpose of the current study was twofold: (1) to develop a computer-based protocol to assess interpersonal deictic frames across three levels of complexity (i.e., simple, interchange, and double interchange); and (2) to evaluate the role of emotion types and the context in situations that require EPT. Participants included 101 undergraduate students; results showed that the number of errors and the latency to respond increased as a function of the complexity of the relations, with the simplest relations having the fewest errors and the shortest latency to respond. In addition, participants made more errors when responding to items in which all agents were experiencing a similar emotion evoked by the same stimuli. Taken together, these results suggest that a combination of emotion type and the target stimulus may affect performance on EPT tasks.